Design and simulation of high efficiency rectangular microstrip patch antenna using artificial intelligence for 6G era - Saad A. Ayoob; Firas S. Alsharbaty; Amina N. Hammodat (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Sixth-generation (6G) applications require ultra-speed and large-capacity wireless communication services. Millimeter wave technology can be used to satisfy these requirements, especially at 28 GHz. This paper study used the Ansys® high-frequency structure simulator (HFSS) to design and simulate rectangular and slotted rectangular microstrip patch antennas (MSPAs) at 28 GHz. The proposed designs contained a Rogers RT/Duroid® 5,880 substrate with a dielectric constant (εr) of 2.2 and a loss tangent of 0.0009. The performance of both the proposed antennas was compared to determine which was more efficient. This present study also used an adaptive network-based fuzzy inference system (ANFIS) to determine the optimal frequency and gain. The main objective of the manuscript is to use artificial intelligence (AI) to obtain the best design results for MSPA. The results indicated, with the use of AI, the gain of the rectangular and slotted antennas, was 6.3943 and 6.3094 dB at an efficiency of 98.338% and 98.651%, respectively.